A self-cleaning surface based on UV-activatable, AgCl micropumps for bacterial killing and removal. Issue 50 (1st June 2022) - Liu, Peng; Quan, Kecheng; Liu, Miaomiao; Wang, Huaguang; van der Mei, Henny C.; Busscher, Henk J.; Zhang, Zexin
Abstract : AgCl microparticles immobilized on a surface release Ag + ions to kill attached bacteria and act as micropumps to remove dead bacteria from the surface. Abstract : We report a self-cleaning, bacterial killing surface by immobilization of AgCl microparticles on a surface, acting as chemical micropumps. The surface shows a high bacterial killing efficacy of attached bacteria and exhibits sustainable removal of bacteria as a result of UV-activatable micropumping originating from the photocatalytic reaction of AgCl microparticles. Our work provides an advance in the sustainable use of bacterial contact-killing surfaces stricto sensu through removal of dead bacteria and debris that may shield contact-killing sites.